The Paradox of Official Secrets: Does It Help or Hurt Consumer Trust? - Olsen,Lill Julie Alm; Gunnarsson,Linnéa; Kristiansen,Elin Boberg (LBMG Strategic Brand Management - Masters Paper Series, 2025)
Purpose: To investigate how revealing the official secrets in different industries influence consumer trust. Methodology: Primary data were collected through a quantitative consumer survey measuring the impact of revealing an official secret on trust. This was complemented by secondary case analyses of Polestar and Kérastase, supported by relevant literature and industry sources to contextualize the findings. Findings: The survey reveals that the impact of revealing an official secret on consumer trust varies across cases and among respondents. Revealing Polestar’s official secret had a significantly positive effect on consumer trust, with the average trust level increasing by 2.1. In contrast, revealing Kérastase’s official secret had an overall neutral impact, with the average trust level increasing by 0.3. This overall neutral impact consists of mixed responses among the respondents, some reported increased trust, while others experienced decreased trust. Research limitations: The research was limited by the scope of respondents’ sample and the number of cases examined, which consequently restricts the generalizability of the findings. Practical implications: The research indicates that revealing an official secret can both help and hurt the brand. Therefore, brand architecture should be approached as a carefully evaluated strategic decision within the managerial context. The varying responses highlight the importance of knowing both your audience and owner, and of finding the right balance between visibility and secrecy to build the highest possible level of trust. Managers should also remain aware of their goals and consider the impact of official secrets on trust, alongside other strategic factors to guide their decision-making and define their strategic direction. Originality/value: This study introduces unexplored research on the phenomenon of official secrets, defined as instances where a brand deliberately hides or downplays its ownership affiliation, by exploring how such secrecy shapes consumer trust. The findings offer valuable insights for managers seeking to navigate the paradox between transparency and strategic secrecy within contemporary brand architecture, adding one dimension in the strategic decision-making. Keywords: Official secrets, Ownership disclosure, Consumer trust, Brand architecture, Transparency Paper typer: Research paper
Keywords: Official secrets; Ownership disclosure; Consumer trust; Brand architecture; Transparency; Brand strategy; Corporate brand visibility; Brand authenticity; Stealth marketing; Brand hiding